3D Metal‐Rich Cu7.2S4/Carbon‐Supported MoS2 Nanosheets for Enhanced Lithium‐Storage Performance. Issue 5 (11th January 2019) - Liu, Zhimin; Qi, Shaopeng; Liu, Guoning; Cheng, Lin; Chen, Jinxi; Lou, Yongbing
Abstract: MoS2 exhibits a high theoretical capacity and has been widely studied as an anode candidate for high‐performance lithium‐ion batteries (LIBs). However, unmodified MoS2 suffers from inherently poor conductivity and poor cycle stability because of the lamellar stack. Herein, a novel core‐shell nanocomposite material (Cu7.2 S4 /C@MoS2 ) was obtained to significantly improve the electrochemical performance of MoS2, where ultra‐thin MoS2 nanosheets were uniformly grown on a three‐dimensional (3D) metal‐rich Cu7.2 S4 /C support by a simple hydrothermal reaction. When employed as an anode for LIBs, the discharge capacity of the 3D core‐shell Cu7.2 S4 /C@MoS2 nanocomposite reached 1527.4 mAh g −1 after 340 cycles at a high current density of 1 A g −1, which is much higher than that of pure MoS2 nanosheets. The excellent electrochemical performance of the nanocomposite demonstrates its potential application in batteries. Abstract : Ultrathin MoS2 nanosheets are uniformly grown on a 3D metal‐rich Cu7.2 S4 /C support by a simple hydrothermal reaction. When employed as an anode for lithium‐ion batteries, the discharge capacity of the core‐shell nanocomposite reaches 1527.4 mAh g −1 after 340 cycles at a high current density of 1 A g −1 .